Genetic consequences of postglacial range expansion in two codistributed rodents (genus Dipodomys) depend on ecology and genetic locus. Issue 1 (13th December 2014) - Jezkova, Tereza; Riddle, Brett R.; Card, Daren C.; Schield, Drew R.; Eckstut, Mallory E.; Castoe, Todd A.
Abstract How does range expansion affect genetic diversity in species with different ecologies, and do different types of genetic markers lead to different conclusions? We addressed these questions by assessing the genetic consequences of postglacial range expansion using mitochondrial DNA (mtDNA) and nuclear restriction site‐associated DNA (RAD) sequencing in two congeneric and codistributed rodents with different ecological characteristics: the desert kangaroo rat (Dipodomys deserti), a sand specialist, and the Merriam's kangaroo rat (Dipodomys merriami), a substrate generalist. For each species, we compared genetic variation between populations that retained stable distributions throughout glacial periods and those inferred to have expanded since the last glacial maximum. Our results suggest that expanded populations of both species experienced a loss of private mtDNA haplotypes and differentiation among populations, as well as a loss of nuclear single‐nucleotide polymorphism (SNP) private alleles and polymorphic loci. However, only D. deserti experienced a loss of nucleotide diversity (both mtDNA and nuclear) and nuclear heterozygosity. For all indices of diversity and differentiation that showed reduced values in the expanded areas, D. deserti populations experienced a greater degree of loss than did D. merriami populations. Additionally, patterns of loss in genetic diversity in expanded populations were substantially less extreme (by two orders of magnitude in some cases) for nuclear SNPs in both species compared to that observed for mitochondrial data. Our results demonstrate that ecological characteristics may play a role in determining genetic variation associated with range expansions, yet mtDNA diversity loss is not necessarily accompanied by a matched magnitude of loss in nuclear diversity.